Review Of Workforce Needs In The Filing Section Based On The ABK – Kes Method At RSJD Dr. Arif Zainudin Surakarta In 2024 - Cahyaningrum, Nopita; Andriani, Rika; Rahayuningsih, Lilik Anggar Sri; Refin, Joanne Kayla (Procedia of Engineering and Life Science, 2024)
The ABK - Kes method is one way of calculating health human resource needs based on the workload carried out by each type of SDMK in accordance with their main duties and functions. Dr Arif Zainudin Surakarta Regional Mental Hospital has 2 filing officers. There are several problems including filing officers having to sort documents manually, the transition of manual medical records to electronic medical records, and limited medical record document folders in medicolegal services. This study aims to determine the number of labour requirements in the medical record unit of the filing section using the ABK - Kes method. This research is a descriptive research, with a cross sectional approach. The subjects in this research are 2 filing officers while the object in this research is the workload of filing officers. Data collection methods were carried out by observation and interview. The results of this research are a health facility of the type of regional psychiatric hospital owned by the Central Java provincial government with the type of SDMK medical records unit in the filing section, available work time of 75.600 minutes/year, workload components totalling 13 main tasks and 3 additional tasks, workload standards of 285.773 minutes/year, FTP value of 2.75% and STP value of 1.03 and the need for SDMK in the filing section after being calculated using the ABK - Kes method is 4 officers. The number of officers of the medical record unit in the filing section at Dr Arif Zainudin Surakarta Hospital currently amounts to 2 officers, from the results of calculations using the ABK-KES method resulting in 4 officers. The suggestion that researchers can give is that they should add 2 medical record officers in the filing section, so that the workload of filing officers is not high which will result in the quality of officer performance.